The Role of Immunotherapy in Non-transplant Eligible Multiple Myeloma - Bobin, Arthur; Gardeney, Hélène; Sabirou, Florence; Gruchet, Cécile; Lévy, Anthony; Nsiala, Laly; Cailly, Laura; Tomowiak, Cécile; Torregrosa, Jose; Guidez, Stéphanie; Leleu, Xavier (Frontiers in Oncology, 2020)
Non-transplant eligible (NSCT) multiple myeloma are increasing as the global population is aging and with prolonged survival in line with the modern treatment options. Yet, treating these patients remains a challenge especially because of a marked heterogeneity of the population and an increased susceptibility to treatment toxicity. Indeed, NSCT MM is currently treated under a balance between efficacy and safety paradigm that must be considered at all time throughout the treatment line history. Therefore, younger and older patients were historically treated in a very different way, even though the field has drastically improved the safety profile of most anti-myeloma drugs over the years. The emergence of immunotherapy (IT) widened the therapeutic options available to MM overall, has allowed a switch from a need for safety/efficacy balance to IT available to all patients independently of frailty features at optimal dose and therefore optimal activity with no increase in safety issues. Among the novel anti-myeloma IT agents anti-CD38 monoclonal antibodies are now becoming the new backbone of treatment for all MM, including NSCT patients, and including even the more frail, in association with lenalidomide and dexamethasone. On top, several new IT drugs are currently being developed and investigated such as other naïve IT anti CD38, plus other targets, and new armed cellular and antibody-based IT such as CAR-T cells, bispecific T cell engager, or antibody drug conjugate targeting BCMA. One would expect that IT will ultimately change and even transform the MM landscape, even for older and elderly patients. IT represents a shift in treatment paradigm in MM, independently of their frail status, as IT provides truly efficient drugs with a very favorable safety profile. NSCT MM patients will now have the opportunity to be treated at most optimal best active treatment dose with IT integrated into treatment paradigm and regimens.